(S)-(-)-N-[2-(3-Hydroxy-2-oxo-2, 3-dihydro-1H-indol-3-yl)-ethyl]-acetamide inhibits melanoma cell growth through inducing apoptosis and autophagy. (2nd October 2021) - Wang, Dawei; Li, Qing; Wang, Yue; Jiang, Yuanchun
Abstract: Purpose: Melanoma is the most lethal form of skin cancer with the incidence drastically increasing over the past several decades. ( S )-(-)-N-[2-(3-Hydroxy-2-oxo-2, 3-dihydro-1 H -indol-3-yl)-ethyl]-acetamide (SA) was a new compound isolated from the leaves of Selaginella pulvinata, with potent activities to inhibit the proliferation of SK-mel-110 cells. This study was to further investigate effects of SA against melanoma and explore its underlying mechanisms. Methods: B16 cells were treated with different concentrations of SA. Tumour model was established by injecting B16 cells into C57 mice subcutaneously. MTT and LDH assays were used to detect effects of SA on cell viability. ELISA assay, Annexin V/PI staining and TUNEL assay were used to detect apoptosis. RT-qPCR and western blot were used to detect the expression of genes and proteins, respectively. Results: SA significantly inhibited the proliferation of melanoma cells and induced the apoptosis as well as autophagy, which may be associated with PI3K/Akt and MAPK signal pathways. Moreover, SA treatment significantly slowed melanoma tumour growth, evidenced by decreased tumour volume and tumour weight. Conclusions: Our data suggested that SA could be developed as a potential anti-tumour drug against melanoma.